(untitled) (Journal of Asian Development Studies, 2026)
This paper examines the impact of digital finance on the economic growth of BRICS countries (Brazil, Russia, India, China, and South Africa) from 2000 to 2023, emphasising the role of financial development as a moderator. Digital finance enhances financial inclusion, lowers transaction costs, and improves resource allocation, which is reflected in mobile subscriptions. The study employs a quantitative design using secondary panel data from the World Bank, utilising a log-linear regression model that incorporates various factors such as government expenditure, employment, trade openness, inflation rates, and foreign direct investment (FDI). Findings reveal a significant positive effect of digital finance on economic growth, with a stronger financial development framework amplifying this effect. The research suggests that enhancing the existing financial system is crucial for maximising the advantages of digital banking in poorer nations. It emphasises the importance of investing in digital infrastructure, financial literacy, and inclusive credit markets to leverage digital finance for sustainable growth in BRICS and other emerging markets.